The Importance of Postcolonialism in Learning History Amid the Challenges of Globalization - Sariyatun, Gusti Garnis Sasmita, Hermanu Joebagio dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Social change in the context of social deviations that occur in the community is a necessityall the time. The relativeity of deviant behavior encourages social control by thegovernment. Regularity is the standard of social welfare. So education as one of the socialcontrol institutions is preventiv in responding to various changes in the era of globalization.Education development, especially historical learning is a form of acculturation ofmodernism and local genius community. So in the frame of poskoloniality, Historicallearning actually leads to peace building. So western colonialism can be viewed as a formof colonialism that stimulates the development of critical intellectuals which in the era ofglobal cultural hegemony determine the quality of national education. So the ideal historicallesson will be born when perception is built from the